2016
DOI: 10.1055/s-0042-113143
|View full text |Cite
|
Sign up to set email alerts
|

Alkoholabhängigkeit in der primärärztlichen Versorgung: Welche Patienten werden erkannt?

Abstract: Zusammenfassung Ziel: Der Zugang zum Suchthilfesystem wird erschwert, wenn der Hausarzt die Alkoholabhängigkeit des Patienten nicht erkennt. Wir überprüften, wie gut hausärztliche und standardisierte klinische Diagnostik übereinstimmen. Methodik: Die deutsche Stichprobe der europaweiten APC-Studie umfasst N=1 356 Patienten, für die Diagnosestellungen durch N=76 Hausärzte bzw. das Composite International Diagnostic Interview (CIDI) vorliegen. Beide Diagnosen wurden mittels gewichteter Regressionsanalyse vergli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Previous estimates of treatment rates in Germany were based on diagnoses from aggregated data, such as hospital diagnosis statistics and the diagnosis portal of the Central Institute of Statutory Health Insurance Physicians [Zentralinstitut für die kassenärztliche Versorgung (Zi)] ( 16 ), were derived from per capita consumption ( 17 ) or based on survey data ( 15 ). In addition, several studies reported differences in diagnoses depending on the setting and the diagnostic instrument ( 18 , 19 ). A study among primary care patients showed that general practitioners diagnose alcohol dependence more often in male and older patients compared to a standardized, self-administered closed-ended clinical diagnostic questionnaire ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous estimates of treatment rates in Germany were based on diagnoses from aggregated data, such as hospital diagnosis statistics and the diagnosis portal of the Central Institute of Statutory Health Insurance Physicians [Zentralinstitut für die kassenärztliche Versorgung (Zi)] ( 16 ), were derived from per capita consumption ( 17 ) or based on survey data ( 15 ). In addition, several studies reported differences in diagnoses depending on the setting and the diagnostic instrument ( 18 , 19 ). A study among primary care patients showed that general practitioners diagnose alcohol dependence more often in male and older patients compared to a standardized, self-administered closed-ended clinical diagnostic questionnaire ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies reported differences in diagnoses depending on the setting and the diagnostic instrument ( 18 , 19 ). A study among primary care patients showed that general practitioners diagnose alcohol dependence more often in male and older patients compared to a standardized, self-administered closed-ended clinical diagnostic questionnaire ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Die darin enthaltenen Behandlungskosten für SUDs könnten deutlich höher ausfallen, da SUDs selbst von behandelnden Hausärztinnen und Hausärzten oft nicht oder erst nach Jahren erkannt werden (z. B. Alkoholabhängigkeit: [13]) und mit ca. 500 000 Personen pro Jahr [14] nur ein Bruchteil der ca.…”
Section: Introductionunclassified